The challenges of modulating the 'rest and digest' system: acetylcholine receptors as drug targets. Issue 1 (January 2017) - VanPatten, Sonya; Al-Abed, Yousef
Highlights: The acetylcholine system has a major role in the autonomic nervous system. Acetylcholine receptors are targets for many clinically approved drugs. Receptor subtype specificity can influence which downstream effects are modulated. Levels of regulation tune the acetylcholine system to existing biologic conditions. This intricate regulation must be taken into consideration in ligand design. Abstract : Acetylcholine, a major neurotransmitter of the parasympathetic and sympathetic nervous systems, was discovered in the early 1900s. Over the years, researchers have revealed much about its regulation, properties of its receptors and features of the downstream signaling that influence its terminal effects. The acetylcholine system, traditionally associated with neuromuscular communication, is now known to play a crucial part in modulation of the immune system and other 'rest and digest' effects. Recent research seeks to elucidate the system's role in brain functions including cognition, sleep, arousal, motivation, reward and pain. We highlight clinically approved and experimental drugs that modulate the acetylcholine receptors. The complexities in targeting the acetylcholine receptors are vast and finding future indications for drug development associated with specific acetylcholine receptors remains a challenge. Abstract : Acetylcholine receptors serve as important targets for modulating effects of the autonomic nervous system. Discovery of the specific level of promiscuity and specificity necessary to target desired downstream effects remains the goal.